Putting electoral competition where it belongs: comparing vote-based measures of electoral competition - Aiko Wagner; Werner Krause (Journal of Elections, Public Opinion and Parties, 2021)
Electoral competition is a cornerstone of representative democracies. However, measuring its extent and intensity constitutes a challenging task for the discipline. Based on multilevel conceptualizations, we discuss three different measures of political competition (electoral volatility, vote switching, and voters' availability) and their relation to each other. We argue that electoral volatility and vote switching as indicators of electoral competitiveness tend to misestimate the degree of competition in multiparty systems. As an alternative, we propose focusing on the individual's propensity to vote for different parties, i.e. electoral availability. Using data provided by the European Election Studies, we compare availability to electoral volatility and vote switching in the framework of necessary and sufficient conditions. Our regression results show that operationalizing electoral competitiveness based on voter availability – which is increasingly retrievable from cross-national voter surveys – helps to avoid type-II errors, i.e. identifying competitive elections as less or non-competitive.
doi:10.7910/DVN/1LYGLD
Keywords: 300; political competition; volatility; electoral behavior; party systems; availability; vote switching